2012
DOI: 10.1101/lm.023937.111
|View full text |Cite
|
Sign up to set email alerts
|

Impaired associative taste learning and abnormal brain activation in kinase-defective eEF2K mice

Abstract: Memory consolidation is defined temporally based on pharmacological interventions such as inhibitors of mRNA translation (molecular consolidation) or post-acquisition deactivation of specific brain regions (systems level consolidation). However, the relationship between molecular and systems consolidation are poorly understood. Molecular consolidation mechanisms involved in translation initiation and elongation have previously been studied in the cortex using taste-learning paradigms. For example, the levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 45 publications
5
58
1
Order By: Relevance
“…The role of eEF2 phosphorylation in processing associative memory at the systems level was also examined using manganese-enhanced magnetic resonance imaging (MEMRI). eEF2K-deficient mice had a more diffuse accumulation of Mn 2+ following CTA acquisition as compared with wild-type mice (Gildish et al 2012), suggesting that the regulation of eEF2 participates in the regulation of brain activation patterns during associative memory formation.…”
Section: Eef2 and Taste Learningmentioning
confidence: 94%
See 2 more Smart Citations
“…The role of eEF2 phosphorylation in processing associative memory at the systems level was also examined using manganese-enhanced magnetic resonance imaging (MEMRI). eEF2K-deficient mice had a more diffuse accumulation of Mn 2+ following CTA acquisition as compared with wild-type mice (Gildish et al 2012), suggesting that the regulation of eEF2 participates in the regulation of brain activation patterns during associative memory formation.…”
Section: Eef2 and Taste Learningmentioning
confidence: 94%
“…Currently, the term consolidation or off-line processing of a given memory consists of two distinct processes: aspects of molecular consolidation, completed within hours after training, and system consolidation, taking several days or more, and thought to involve reorganization of brain circuits. However, the relationship between the two types of consolidation is poorly understood (Gildish et al 2012).…”
Section: Molecular Memory Consolidationmentioning
confidence: 99%
See 1 more Smart Citation
“…Park et al [59] showed that eEF2K plays an important role in the synthesis of Arc/Arg3.1, a protein involved in neurotransmitter receptor trafficking and in longterm depression, a process that reflects changes in synaptic strength. Gildish et al [60] used mice in which an inactivating mutation was introduced into the eEF2K gene. Their data showed that such animals displayed defective associative taste learning in a learning paradigm termed conditioned taste aversion.…”
Section: Neurological Roles Of Eef2kmentioning
confidence: 99%
“…Critically, eEF2K is activated by calcium/calmodulin and consequently regulated by neural activity (Nairn et al 2001). Indeed, eEF2K has been implicated as a control point in the synthesis of proteins important for memory since either increasing or decreasing eEF2K activity affects memory formation in distinct plasticity paradigms (Im et al 2009;Gildish et al 2012). eEF2K has been shown to be particularly important in conveying information mediated by spontaneous release (Sutton et al 2007) and signaling though mGluR receptors (Park et al 2008).…”
Section: S6 Kinase Targetsmentioning
confidence: 99%